2013
DOI: 10.1002/cssc.201300874
|View full text |Cite
|
Sign up to set email alerts
|

Ferric chloride‐Graphite Intercalation Compounds as Anode Materials for Li‐ion Batteries

Abstract: Ferric chloride-graphite intercalation compounds (FeCl3 -GICs) with stage 1 and stage 2 structures were synthesized by reacting FeCl3 and expanded graphite (EG) in air in a stainless-steel autoclave. As rechargeable Li-ion batteries, these FeCl3 -GICs exhibit high capacity, excellent cycling stability, and superior rate capability, which could be attributed to their unique intercalation features. This work may enable new possibilities for the fabrication of Li-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 29 publications
6
45
0
Order By: Relevance
“…Even at the higher current density of 5,000 mA·g −1 , the PGS-2-1000 electrode still delivers a capacity as high as 426.4 mAh·g −1 after the 50th cycle, which is still higher than the theoretical capacity of graphite (372 mAh·g −1) . Besides, the value is far superior to those of the reported hollow carbon nanofibers [54][55][56], hollow carbon nanospheres [57], graphene nanosheets [58], amorphous carbon [59], and other carbon-based anode materials [60][61][62][63][64][65][66]. Furthermore, the Coulombic efficiency is always 100% for all the current rates.…”
Section: Resultsmentioning
confidence: 74%
“…Even at the higher current density of 5,000 mA·g −1 , the PGS-2-1000 electrode still delivers a capacity as high as 426.4 mAh·g −1 after the 50th cycle, which is still higher than the theoretical capacity of graphite (372 mAh·g −1) . Besides, the value is far superior to those of the reported hollow carbon nanofibers [54][55][56], hollow carbon nanospheres [57], graphene nanosheets [58], amorphous carbon [59], and other carbon-based anode materials [60][61][62][63][64][65][66]. Furthermore, the Coulombic efficiency is always 100% for all the current rates.…”
Section: Resultsmentioning
confidence: 74%
“…Pristine graphite shows a typical XRD pattern with two peaks indexed to (002) Fe2O3 or Fe3O4 in GICs, the quantity is too little to be detected by XRD. 22,35 The d-spacing of FeCl3-GICs is significantly increased to 0.96 nm from 0.33 nm for graphite. The accordion-like structure is observed in their SEM images (Fig.…”
Section: Graphene Sheets Prepared By Ultrasonic Exfoliation Of Gicsmentioning
confidence: 97%
“…The stage structure of FeCl3-GICs is determined by identifying the component and structure of G peak. 22,36 Intercalation of FeCl3 into the intra-gallery of graphite results in a large blue shift for G peak from 1580 to 1621 cm -1 , which is attributed to the doping effect induced by the charge transfer from graphite to FeCl3. Similar results were reported and suggested that graphene sheet is flanked on both sides by FeCl3 in the stage 1 FeCl3-GICs.…”
Section: Graphene Sheets Prepared By Ultrasonic Exfoliation Of Gicsmentioning
confidence: 99%
“…Expanded graphite (EG), the most important graphite derivative, has aroused considerable interest [2][3][4][5][6]. Compared with graphite, EG exhibits much higher capacity owing to its larger pores, larger surface area, high conductivity, structural defects, chemical stability and extra space for lithium-ion storage.…”
Section: Introductionmentioning
confidence: 99%